THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE TOWARDS ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) WITH COMMITMENT ORGANIZATION AS A MEDIATION VARIABLE (PT OFFICE POST MEDAN) - Enjel Sianturi, Hermin; Aditi, Bunga; Arief Nasution, Aulia (Berajah Journal, 2024)
This research aims to determine the influence of knowledge management and organizational culture on organizational commitment, to find out whether organizational commitment mediates the influence of knowledge management and organizational culture on organizational citizenship behavior (OCB) at PT. Medan Post Office. The population in this study was 116 respondents and used a saturated sampling technique. The analysis technique used is path analysis. The results of the research show that transformational leadership style has a positive and significant effect on organizational commitment, organizational culture has a positive and significant effect on organizational commitment, transformational leadership style has a positive and significant effect on organizational citizenship behavior (OCB), organizational culture has no effect on organizational citizenship behavior (OCB). ), organizational commitment has no effect on organizational citizenship behavior (OCB), organizational commitment does not mediate the effect of transformational leadership style on organizational citizenship behavior (OCB) and organizational commitment does not mediate the effect of organizational culture on organizational citizenship behavior (OCB ) at PT. Medan Post Office.